Pengaruh Fortifikasi Zat Besi Menggunakan Fe-Sulfat, Fe-Fumarat dan Na Fe EDTA Terhadap Kualitas Sensori Produk-Produk Olahan Tepung Terigu - Dede Robiatul Adawiyah; Tjahja Muhandri; Subarna Subarna; Sugiyono Sugiyono (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
The consumption of wheat flour in Indonesia is very high reaching 5.9 million tons during year 2016 and tends to increase steadily every year. The National Standardization Agency of Indonesia (BSN) of Wheat Flour (2009) requires the fortification with minimum iron of 50 ppm (as Fe-elemental). Study conducted byIndonesian ministry of health based on WHO recommendation (2006) states that for wheat consumption 75-149 g/day, fortificication wheat flour with iron should be as much as 60 ppm (in the form of Fe-fumarate or Fe-sulphate) or 40 ppm (in the form of NaFeEDTA compound), zinc 55 ppm (in the form of zinc oxide compound), and folic acid 2.6 ppm. The aim of this research was to evaluate the effect of fe fortification using 3 types of fe fortifcants: Ferous fumarat, Ferous sulfat and NaFeEDTA), zinc (in form of Zn oksida), vitamin B1, vitamin B2, asam folat (as premix) on sensory quality of wheat flour products such as bread, pao, cookies, noodle and macaroni. The result showed that Fe fortification using Fe-sulfat, Fe-fumarat dan Na Fe-EDTA in wheat flour did not significantly affect sensory properties of breads and pao. For cookies, NaFeEDTA slightly affect on texture (slightly harder). For noodle and macaroni, NaFeEDTA dan ferous-sulfat affect on color of productss to become darker. Overall, fe-fumarat was recommended fortificant for iron fortification of wheat flour with the lowest effect on sensory properties of wheat products.